Withdrawals of electric power and energy national interconnected contract without back care system regulated market held by the peruvian electric distribution companies: Background: Causes and consequences - Vignolo Cueva, Giancarlo (2016)
The subject of this article is to show an overview of a problem that occurred in the Peruvian Electricity Sector in 2004 and, unfortunately, still produces practical and legal effects in the current system. We refer to the “physical withdrawals of capacity and energy from the SEIN for the attention of the regulated market”, by the different distribution companies without having a PPA signed and valid with any generating power company.